The economic and marketing analysis of the postharvest of a unique Hungarian product, the pear from Kunfehértó (2001–2002) - Ferencz, Árpád; Nótári, Márta (Acta Agraria Kaposváriensis, 2003)
We have viewed a business in the South Plain Region from an economic point of view. The main activity there is pear growing and storage. Four varieties of different time of ripening and storing are grown there. We have measured all the relevant activities, worked out local normatives and prepared a detailed technology. The economic evaluation was based on this data. Activities, like disinfection, pre-storage disinfection and selection, in-storing and out-storing, classification after storage, packaging, as well as loading trucks, were monitored by variety. Storage loss was determined and widely varied according to varieties, length of storage and time of out-storing. Different varieties resulted in different quality classes after storage. Price depended on the quality classes. Economic evaluation was carried out when all the relevant costs and revenues were known. Fixed and variable costs of storage were determined, break-even point was calculate and the market position of the product was evaluated.
Keywords: pear-storage; economic evaluation; unique Hungarian product; postharvest